(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
The essence of this article is that there are problems in machine-building industries in our country with the installation of equipment imported from foreign companies, maintenance of their parts and mechanisms, and their repair or replacement. The importance of this problem in the localization of the automotive industry and the calculation of residual resources, new models and methods of accurate and perfect operation, replacement with new ones and the introduction of activities of centralization of their service have been highlighted. In addition to the article, there is talk about other methods in this field.